2023
DOI: 10.3389/fgene.2022.1070783
|View full text |Cite
|
Sign up to set email alerts
|

Distinct traces of mixed ancestry in western commercial pig genomes following gene flow from Chinese indigenous breeds

Abstract: Studying gene flow between different livestock breeds will benefit the discovery of genes related to production traits and provide insight into human historical breeding. Chinese pigs have played an indispensable role in the breeding of Western commercial pigs. However, the differences in the timing and volume of the contribution of pigs from different Chinese regions to Western pigs are not yet apparent. In this paper, we combine the whole-genome sequencing data of 592 pigs from different studies and illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…ADMIXTURE ancestry composition analysis showed that the Chinese and Western pig breeds had two differentiated clusters when K = 2, indicating different ancestral lineages. This is consistent with previous reports indicating that European and Chinese pig breeds have different ancestral origins [ 8 , 20 ]. Wang et al [ 8 ] used a 60 K SNP chip to study three pig breeds in Jiangxi province and found that Chinese and European pigs were clustered into two independent branches, whereas the Chinese–European hybrid breed (Sutai) was located in the middle between the European and Chinese branches in the NJ tree; the obvious difference between Chinese and European pig breeds was also reflected in the PCA diagram.…”
Section: Discussionsupporting
confidence: 93%
“…ADMIXTURE ancestry composition analysis showed that the Chinese and Western pig breeds had two differentiated clusters when K = 2, indicating different ancestral lineages. This is consistent with previous reports indicating that European and Chinese pig breeds have different ancestral origins [ 8 , 20 ]. Wang et al [ 8 ] used a 60 K SNP chip to study three pig breeds in Jiangxi province and found that Chinese and European pigs were clustered into two independent branches, whereas the Chinese–European hybrid breed (Sutai) was located in the middle between the European and Chinese branches in the NJ tree; the obvious difference between Chinese and European pig breeds was also reflected in the PCA diagram.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the increasing evidence highlighting introgression between Asian and European pigs (Bosse, Megens, Frantz, et al 2014; Peng et al 2023), the extent and relative contributions of introgressed variants in pig domestication remain inadequately explored. A comprehensive catalog of variants from a diverse set of animals enabled us to reveal significant signals of genetic introgression between Chinese and European pig breeds (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Chinese indigenous pigs, we further classified the pigs based on their geographical origins proposed in previous studies (Zheng et al 2022; Peng et al 2023), resulting in the following subgroups: Southern Chinese (SCN, n = 18), Eastern Chinese (ECN, n = 55), Northern Chinese (NCN, n = 42), and Southwestern Chinese indigenous pigs (SWCN, n = 45). Supplementary Table S1 provides the detailed information of the samples, including the sequencing platforms, accession numbers, sample sizes, and average sequencing coverage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations